Analysis of CRISPR-Cas System in Streptococcus thermophilus and Its Application - Hao, Mengyuan; Cui, Yanhua; Qu, Xiaojun (Frontiers in Microbiology, 2018)
CRISPR-Cas (Clustered regularly interspaced short palindromic repeats-CRISPR associated proteins) loci, which provide a specific immunity against exogenous elements, are hypervariable among distinct prokaryotes. Based on previous researches, this review focuses on concluding systematical genome editing protocols in Streptococcus thermophilus. Firstly, its protocols and optimized conditions in gene editing are introduced. What’s more, classification and diversity analyses of S. thermophilus CRISPR-Cas benefit the further understanding of evolution relationship among Streptococcus. Ability of its foreign segment integration and spacer source analyses also indicate a new direction of phage resistance. Above all, all of these point out its potential to be regarded as another model system other than type Ⅱ CRISPR-Cas in Streptococcus pyogenes.